Needs assessment: construction management doctoral programs in the United States - Gunderson, David E., author; Gloeckner, Gene, advisor; Grosse, Larry W., advisor; Davies, Timothy G., committee member; Khattab, Mostafa M., committee member (Colorado State University. Libraries, 2005)
Prior to July 1, 2005 there were no doctoral degree programs in the United States focusing solely on construction management. Along with the one construction management doctoral degree there are at least 16 universities self-reporting to have a doctoral degree allowing for a construction related emphasis. Many of these programs offer a doctoral degree in engineering, architecture, technology, or education. Even though construction education programs were established as early as 1926, the majority of the oldest undergraduate construction education programs were established between 50 and 60 years ago. Construction education programs are maturing with the Associated Schools of Construction (ASC) reporting that 31 (55.4%) out of 56 American Council for Construction Education (ACCE) accredited programs offer a master's degree. Eighteen (58.1%) of these master's degrees have the word "construction" in the degree title. While construction management programs are interdisciplinary in their content drawing on engineering, architecture, technology, and business, they are a unique discipline. Even the Department of Educational Statistics classifies Construction Management as a distinctive program in their Classification of Instructional Programs under category 52 (Business, Management, Marketing, and Related Support Services). During the 2004 - 2005 academic year 100% of the ASC advertisements for open construction education faculty positions required or preferred the candidate to have a doctoral degree. Many of the open positions go unfilled because the demand for faculty members to teach in construction education programs exceeds the available supply. There are five primary qualification areas for candidates around which search committees evaluate individuals to fill open faculty positions in construction education: doctoral degree, experience in the construction industry, the ability to be a good teacher, the ability to be a good researcher, and professional registration or certification. This research confirms what is found in existing literature: about half of faculty members teaching in construction education programs have a doctoral degree and meet the current qualification requirements. Interviews with construction education department heads and a survey completed by faculty teaching in ACCE accredited postsecondary construction education programs very clearly indicate that construction management doctoral programs are needed in the United States.
Keywords: curricula; teaching; higher education; university faculty; graduate studies; polls and surveys; studies; curriculum development; students; accreditation; core curriculum; academic degrees